INDICATORS OF SCIENCE APTITUDE IN SOME NIGERIAN SECONDARY SCHOOL GIRLS (1973)
This thesis investigated some mental, personality and environmental variables among Form One girls in a secondary school as possible predictors of science aptitude. The variables were mental abilities, scholastic ability, interest in science, reading habits, personality traits and home environment. The variables were measured by using selected I-D aptitude tests-from Test Development and Research Office, West African Examinations Council, Lagos, a modified Edwards Personality Preference Schedule (EPPS) and a home background questionnaire. Science achievement was measured by a Science Achievement test, of the multiple-choice objective type, based on the science syllabus of the school for the year, and the normal school examinations. Correlations between the variables and science achievement were computed. Verbal ability, ability to grasp science information, mechanical reasoning, reading ability, ability to do graph work, and high achievement in other school subjects correlated positively and significantly with science achievement in the first year while arithmetical ability, ability to read tables, the environment, parents, professions, personality traits, and interest in science did not. Beyond the first year, correlations became insignificant. The results are explained in terms of the equalising effects of the school environment which tends to overshadow differences due to home environment and previous schooling.